Development of Interactive Media "Aku Popo Antik" to Improve Science Comprehension Ability of Human Digestive System Material in Class V at SDN 1 Rantepao - Ratnawati Ratnawati; Abdullah Sinring; Sandra Sukmaning Adji (EduLine: Journal of Education and Learning Innovation, 2023)
This study aims to determine the development, effectiveness and feasibility of the product of interactive media "Aku Popo Antik" on the content of science learning material of the Human Digestive System in class V at SDN 1 Rantepao. This type of research is included in Research & Development (R&D) or research and development, and aims to produce a product by developing new ideas or improving certain existing products through certain procedures and steps. The development model used in this study uses the Robert Maribe Brach model and the ADDIE approach: analysis, design, development, implementation, and evaluation. Data were obtained through questionnaires (validation, practicality, and attractiveness), tests to assess mastery of competencies that have been learned as a form of field test results conducted using interactive media "Aku Popo Antik", and observations to help analyze the learning situation, learning needs, facilities and infrastructure, Data processing uses qualitative and quantitative descriptive analysis. The results showed that: (1) The level of student need for media is very high, considering that the use of media is very influential on student understanding, this can be seen from students who obtained scores above KKM 70 which were still low before the use of media. (2) Increased understanding, especially of Food Digestion System material. This statement is evidenced by the results of student posttests. (3) The media product "Aku Popo Antik" is declared valid and can be used after going through material and media validation testing by experts through questionnaire instruments. (4) The media is able to maximize the quality of learning and is considered practical in terms of usage techniques, material presentation, and design. (5) The media product "Aku Popo Antik" is said to be attractive because it is accompanied by various interesting features that can be used by students for online or offline learning activities, both at school and at home.